An interview study to identify circulating nurses' nontechnical skills. Issue 3 (7th March 2022) - Kalantari, Reza; Zamanian, Zahra; Hasanshahi, Mehdi; Faghihi, Seyed Ali Akbar; Niakan, Mohammad Hadi; Jamali, Jamshid; Gheysari, Somayeh
Abstract: Aim: Non‐technical skills are component features of human factors whose defects can lead to surgical errors and adverse events. Circulating nurses need to deploy non‐technical skills for safe and efficient performance. This study aimed to identify circulating nurses' non‐technical skills. Methods: This interview study was conducted on 29 operating room personnel. Semi‐structured interviews were used for data collection. The prepared annotated transcripts were analysed using the content analysis method by a human factors specialist under the supervision of two other researchers. The extracted behaviours were grouped based on meaning and similarity. Results: Six categories of non‐technical skills including leadership, communication, task management, situational awareness, teamwork, and coping were identified as the circulating nurses' key non‐technical skills. The related behaviours were also noted. Conclusion: Non‐technical skills are incorporated in circulating nurses' tasks from the onset to the end of surgery. Thus, these nurses should be aware of the necessary non‐technical skills and positive behaviours to assure a safe surgery.